Revised taxonomic binomials jeopardize protective wildlife legislation - Zhou, Z; Newman, C; Buesching, C; Meng, X; Macdonald, D; Zhou, Y (Wiley, 2016)
Due to revised phylogenies and newly discovered biogeographic distributions, scientific binomials are being amended continuously. Problematic is that wildlife protection legislation tends not to keep pace with these reappraisals, creating a wide range of legislative loopholes and potentially compromising ability to prosecute illegal wildlife trade (IWT). This serious and growing international problem proves particularly challenging in China because binomials used on China's national legislation have not been up-dated since 1989, alongside the enormous issues of IWT in this mega-diverse nation. Here we focus especially on mammals, because these support lucrative criminal markets and receive the greatest international policing efforts; however all protected taxa are vulnerable to this mis-naming ambiguity. To-date, the names of twenty-five threatened species, including eighteen mammals, have become incongruent with Chinese law. Additionally, two primate species, newly discovered within China, have not yet been incorporated into Chinese law. A further, six mammalian species are known by different synonyms between Chinese law and CITES, hindering international policing and compilation of data on IWT. Taxonomic revisions similarly undermine legislation in other mega-diverse countries; posing a critical risk to wildlife protection worldwide. We recommend that scientific binomials must be updated systematically across all 181 CITES signatory nations.